2021
DOI: 10.1609/icwsm.v5i1.14119
|View full text |Cite
|
Sign up to set email alerts
|

Natural Language Processing to the Rescue? Extracting "Situational Awareness" Tweets During Mass Emergency

Abstract: In times of mass emergency, vast amounts of data are generated via computer-mediated communication (CMC) that are difficult to manually cull and organize into a coherent picture. Yet valuable information is broadcast, and can provide useful insight into time- and safety-critical situations if captured and analyzed properly and rapidly. We describe an approach for automatically identifying messages communicated via Twitter that contribute to situational awareness, and explain why it is beneficial for those seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 17 publications
(9 reference statements)
0
32
0
Order By: Relevance
“…While data gathered from online sources have been shown to aid emergency responders in constructing SI (Verma et al 2011;Olteanu, Vieweg, and Castillo 2015), they may entail misinformation (Castillo, Mendoza, and Poblete 2011), false rumors (Starbird et al 2014), polarization of opinions, and echo chambers (Barberá et al 2015), all of which may confound response efforts. We also found that misinformation can seep into the summary sentences.…”
Section: Implications Of Data Source Method and Implementation Choicesmentioning
confidence: 99%
See 2 more Smart Citations
“…While data gathered from online sources have been shown to aid emergency responders in constructing SI (Verma et al 2011;Olteanu, Vieweg, and Castillo 2015), they may entail misinformation (Castillo, Mendoza, and Poblete 2011), false rumors (Starbird et al 2014), polarization of opinions, and echo chambers (Barberá et al 2015), all of which may confound response efforts. We also found that misinformation can seep into the summary sentences.…”
Section: Implications Of Data Source Method and Implementation Choicesmentioning
confidence: 99%
“…This represents a shift in main sources for gaining SI from television, radio, and print media to real-time or near-time updates, e.g., via Twitter, blogs, and online news. Researchers in crisis informatics (Palen and Anderson 2016;Reuter, Hughes, and Kaufhold 2018) have sought computational means to detect and examine crisis-related information from different text-based sources (Verma et al 2011;Abel et al 2011;Tkachenko, Jarvis, and Procter 2017) in a timely and unbiased manner. Using Twitter as a primary source, Verma and colleagues (2011) extracted linguistic features (unigrams, bigrams, parts-of-speech, subjective cues, register, tone) to detect tweets that contain content related to SI.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They studied the behavior of microbloggers by conducting a qualitative analysis of tweets published during a flooding incident. The authors of [11] employed the bags-ofwords method to locate a crisis's data. Various grammatical elements, like Parts-Of-Speech (POS), are influenced by the vocabulary used in Twitter posts.…”
Section: Crisis-related Tweets Classificationmentioning
confidence: 99%
“…We utilise some NLP techniques in the process of query creation and tweet relevance ranking. Other authors report on techniques for classification of 'event' and 'non-event' tweets that deploy shallow linguistic analysis, e.g., (Verma et al 2011) reports on an approach of using linguistic features (e.g., objectivity, impersonality, formality, etc.) for detecting tweets with content relevant to situational awareness during mass emergencies.…”
Section: Related Workmentioning
confidence: 99%